Econometric analysis 5th: Solution manual - Greene, William H. (Prentice Hall, 2012)
• scalar values with italic, lower case letters, as in a or α • column vectors with boldface lower case letters, as in b, • row vectors as transposed column vectors, as in b′, • single population parameters with greek letters, as in β, • sample estimates of parameters with English letters, as in b as an estimate of β, • sample estimates of population parameters with a caret, as in αˆ • matrices with boldface upper case letters, as in M or Σ, • cross section observations with subscript i, time series observations with subscript t.